Effects of the feeding level in early gestation on body reserves and the productive and reproductive performance of primiparous and multiparous sows. (November 2022) - Carrión-López, M.J.; Madrid, J.; Martínez, S.; Hernández, F.; Orengo, J.
Abstract: Early gestation may be the best period for sows to recover body reserve losses from previous lactation. The aim of this study was to investigate the effect of different levels of restricted feeding in early gestation on the body status, productive and reproductive performance, and hormonal-metabolic status of primiparous and multiparous sows. A total of 130 sows were randomly assigned to one of three feeding levels: Treatment I, which sows were fed at the level commonly used from day 3 to 28 of gestation (2.5 kg·d −1 of a diet with 2.18 Mcal NE·kg −1 and 13.72 g CP·kg −1 ), and Treatments II and III, where feed was increased by 25% and 50%, respectively. Sow body status, litter size and weight, early mortalities, reproductive rates, weaning-to-estrus interval, and hormones linked to metabolism were recorded. The highest weight gain, body condition score, and backfat thickness were found in sows fed Treatment III compared to those fed the usual feeding level (Treatment I). No differences among treatment groups were found in litter size or litter weight, although a tendency for more live born piglets and fewer stillbirths was found in sows fed Treatment III. In contrast, litters from sows fed at higher feeding levels had a higher mortality at 72 h compared to those fed at the lowest feeding level (I), which was partly linked to a higher percentage of piglets culled at birth and piglets weighing less than 800 g. There were no differences in conception and farrowing rates, leptin, progesterone, insulin, or cortisol among treatment groups applied in early gestation. In conclusion, increasing the feeding level in sows during early gestation to improve their short-term productive and reproductive performance remains controversial. Further studies are needed to focus on how the restricted feeding level applied could affect the viability and proportion of low-weight piglets. Highlights: The effect of feeding level in early gestation on sow performance was studied. The usual restricted feeding level was increased by 25% and 50%. Sow body reserves improved throughout gestation and at weaning. No clear benefits of increasing the amount of feed in early gestation were found. Research is needed to assess how the feeding level might affect piglet viability.